Numerical investigation of solidification microstructure formation in sequential YSZ droplet impact under supersonic plasma spraying. (August 2020) - Shen, Mingguang; Li, Ben Q.; Bai, Yu
Highlights: Sequential droplet impact with grain growth and impingement is modelled. Typical velocities of crystal growth are within 2 m/s. Solidification time of a single splat on a stainless steel substrate is about 0.5 μs. The undercooling in crystal growth ranges approximately from 150 K to 500 K. Abstract: A coupled CFD and diffuse interface model was developed to predict the dynamic process of solidification microstructure formation of sequential yttria-stabilized zirconia (YSZ) droplet impact under supersonic plasma spraying. The numerical model relies on the explicit finite difference solution of the Navier-Stokes and energy balance equations, coupled with the Cahn-Hilliard equation, to track liquid-gas interface, and of a phase field model for solidification microstructure formation involving polycrystalline growth to trace solid-liquid interface. Extensive simulations, differing in the status of the first droplet and the impacting parameters of the second one, were carried out. The results reveal that solidification microstructure still follows a columnar pattern if the second droplet lands on the first that is just starting spreading, and that the growth direction around the contact region in the second splat will be obviously skewed by fluid flow if the first has been solidified, owing to earlier and easier nucleation on the top surface of the first splat, thus confirming the epitaxial growth across the splat-splat interface. Computed results are also compared with thermal spray experiments, with gratifying agreement obtained.